Development of fibrous preforms for frp tube connections - Fangueiro, Raúl (2009)
This paper describes the experimental work carried on at the University of Minho concerning the design 20 of weft-knitted fleecy fabrics for application in pipe connections produced with composite materials rein- 21 forced by 3D weft-knitted fabric preforms. The specifications of a T tube composite connexion have been 22 established according to the information of the composites producer company involved in the project. 23 The weft-knitted fleecy fabric has been optimized to perform a better mechanical performance, i.e., to 24 increase the stiffness due to the use of straight fleece yarns. Special knitting techniques, developed by 25 the authors, have been applied to produce 3D shaped performs to be impregnated by using RTM tech- 26 niques. A special mould has been produced according to the required geometry. The results of the 27 mechanical tests made on the final produced samples are presented, discussed and compared with those 28 imposed in the initial specifications.